Educating Change Agents: Teaching Leading Change to Young Honduran Women - Charles P. Seeley (Journal of Scholarly Engagement)
Honduras is the second poorest country in Central America. Historically and traditionally, the Honduran culture is characterized by machismo, the societal domination of females by males. Poverty, homicide, high unemployment and chronic underemployment, drug and gang violence, and single mother-led households are facts of life for Hondurans, especially in rural areas. The scholarly activity described in this professional profile was conducted in the midst of the economic, social, and cultural challenges facing young Honduran women. The focus of this scholarly activity was to prepare young Honduran women to be successful as agents of change in spite of the challenges that arise in the cultural and economic setting that characterizes rural Honduras. The author hopes that other academics will respond to the call to take up their domain expertise to make a difference in the lives of those most in need somewhere in the world.